2020
DOI: 10.18517/ijaseit.10.4.11616
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Adoption of Digital Payment System through an Extended Technology Acceptance Model: an Insight from the Indonesian Small and Medium Enterprises

Abstract: Digitalization in the payment system has been promoted by the Indonesian government since the government is targeting to become the largest digital economy in Southeast Asia. However, not all companies can adopt digital payments quickly. Small and Medium Enterprises (SMEs) have many obstacles to adopt innovative technologies, mainly due to a lack of knowledge and resources. On the other hand, many consumers are getting used to digital payments and demanding SMEs to facilitate their transaction processes with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(128 citation statements)
references
References 31 publications
3
54
0
19
Order By: Relevance
“…Consumers can accept new technology if it is perceived as user-friendly and easy to use, so that they can easily adopt it quickly. Najib and Fahma [6] also found that among small business owners, the ease in using digital payment systems makes it easier for them to adopt. Several previous studies [31,45,46] have shown that when consumers choose to compare the latest technology options with the latest technology and find that the latest technology has advantages in its use, their interest in adopting the technology increases.…”
Section: Hypothesis 1 (H1) Performance Expectations Have a Positive mentioning
confidence: 99%
See 3 more Smart Citations
“…Consumers can accept new technology if it is perceived as user-friendly and easy to use, so that they can easily adopt it quickly. Najib and Fahma [6] also found that among small business owners, the ease in using digital payment systems makes it easier for them to adopt. Several previous studies [31,45,46] have shown that when consumers choose to compare the latest technology options with the latest technology and find that the latest technology has advantages in its use, their interest in adopting the technology increases.…”
Section: Hypothesis 1 (H1) Performance Expectations Have a Positive mentioning
confidence: 99%
“…Then they will adopt the new technology in the future, with the hope that its performance will increase [31]. Najib and Fahma [6] also found that performance expectations were a key factor influencing small food processing businesses to adopt digital payment systems. In terms of FinTech adoption, expectations of better performance from small businesses will also affect FinTech adoption.…”
Section: Factor Affecting Fintech Adoption By Small Businessmentioning
confidence: 99%
See 2 more Smart Citations
“…Hasil keterangan partisipan di atas sejalan dengan hasil penelitian Christmastuti et al (2019) yang menyatakan bahwa latar pendidikan pelaku UMKM berpengaruh terhadap penerimaan software akuntansi dan hasil penelitian Suhartanto & Leo (2018) yang menyimpulkan bahwa kurangnya persepsi pelaku UMKM terhadap kemudahan penggunaan teknologi merupakan faktor penyebab para pelaku UMKM enggan menggunakan teknologi tersebut. Secara keseluruhan, hasil penelitian menunjukkan bahwa persepsi kegunaan (perceived usefulness) dan persepsi kemudahan (perceived ease of use) para pelaku UMKM secara simultan memengaruhi sikap dan penerimaan pelaku terhadap penggunaan sistem teknologi informasi sebagaimana dinyatakan Hamid et al (2015), Al-Fahim et al (2016, Jaafreh (2019), Lanlan et al (2019), Najib & Fahma (2020), dan Istanto (2020).…”
Section: Persepsi Kemudahan (Perceived Of Ease To Use)unclassified